EXPERIENCE OF TAXATION OF REAL ESTATE OF INDIVIDUALS IN FOREIGN COUNTRIES AND ITS APPLICATION IN RUSSIA - M. Dement’eva; A. Zakharova; E. Kirova (Вестник университета)
Approaches to the formation of the value of objects of taxation of real estate of individuals in foreign countries and the establishment of tax rates have been examined. An analysis of tax revenues on real estate of individuals in highly developed countries has been carried out. General trends in property taxation of individuals have been identified. Basic provisions, on which modern systems of real estate taxation of individuals are based, have been formulated. Problems of real property taxation in Russia have been identified. Ways of determining the tax base taking into account the world experience and Russian reality have been proposed. Proposals for the application of tax rates and the implementation of the principle of justice have been elaborated.